Microstructure of AISI 316L austenitic stainless steel processed by laser powderbed fusion with different scanning strategies and its evolution upon annealing and thermomechanical processing - Aota, Leonardo Shoji (2021)
Metallic materials processed by laser powder-bed fusion (LPBF) have unique microstructures inherited from out-of-equilibrium solidification and complex termal history. This work reports the possibility of changing the microstructure during LPBF and post-processing of 316L stainless steel. By controlling the process parameters, namely the scanning strategy, we demonstrate the possibility of creating patterned microstructures in this steel. Changing the scanning strategy also affects the residual stresses as well as the defect substructure caused by the high cooling rates. We explore the microstructure/residual stresses relationship to find alternatives to reduce the residual stresses by controlling the microstructure. Upon post-processing annealing, recrystallization nucleation occurs in a non-uniform manner throughout the patterned microstructure, allowing for a linear grain impingement in its early stages, as revealed by applying the microstructural path method (MPM). The active recrystallization mechanisms are revealed and their influence on the non-homogeneous nucleation and recrystallization kinetics is discussed, as well as the possibility of creating engineered microstructures by LPBF processing. Recrystallization nuclei number density is the main factor responsible for the difference in the recrystallization kinetics between different scanning strategies, while particle pinning is responsible for a sluggish kinetics in both cases. The unique microstructures produced by LPBF were cold rolled down to ε = 1, resulting in intense twinning and shear banding. The latter is unusual for such strain in wrought-processed austenitic stainless steels. Upon annealing, the cold-rolled samples show abnormal grain growth, while this phenomenon is absent when annealing is applied directly after LPBF. Abnormal grain growth is triggered by an initial size advantage for || ND grains along particle-depleted regions. These findings allow us for gaining insight on the control of LPBF-processed microstructures through LPBF-processing and post-processing.